Sustainable development and the socially embedded firm : an inquiry into the nature, causes and transformation of structural unsustainability in contemporary liberal capitalism - Voges, Frederik Wilhelm Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil.) -- University of Stellenbosch, 1999.